وبائيات واختلاطات تنظير باطن الرحم - الدالي, عصام; رمضان, لينا; صقر, نوار (Latakia University Journal -Medical Sciences Series, 2015)
إن تنظير باطن الرحم إجراء هام جداً لتشخيص وعلاج العديد من الآفات داخل جوف الرحم مثل البوليبات البطانية – الأورام الليفية تحت المخاطية – التشوهات الخلقية في الرحم – الالتصاقات في بطانة الرحم. و تبرز فائدة التنظير لكونه وسيلة رؤية مباشرة لجوف الرحم . أجريت دراستنا حول اختلاطات تنظير باطن الرحم ونسبتها . وقد اشتمل هذا البحث على 82 مريضة راجعن قسم التوليد وأمراض النساء في مشفى الأسد الجامعي باللاذقية بشكايات : عقم ، نزف تناسلي شاذ , اضطرابات طمثية, اسقاطات متكررة ، ضياع خيط لولب . كانت نسبة اختلاطات تنظير باطن الرحم في دراستنا (4.88% ) وقد كان الاختلاط الأكثر تكراراً هو النزف (بنسبة2.44% )، بينما تساوت نسبة انثقاب الرحم والألم البطني الحاد ( بنسبة 1.22% ) لكل منهما. لم نجد أي اختلافات في نسب الاختلاطات بالنسبة لاستطبابات التنظير المختلفة كما وجدنا أن انعدام الولادات عند المريضة يلعب دوراً كعامل خطورة في ارتفاع نسبة الاختلاطات .إذاً كانت نسبة الاختلاطات في دراستنا قليلة مما يبين أن تنظير باطن الرحم هو وسيلة آمنة مما يشجعنا على التوصية باستخدامها بشكل أوسع حيث تقلل مدة الاستشفاء والكلفة الاقتصادية . Hysteroscopy is a very important procedure to diagnose many lesions inside the uterus like: endometrial polyps, Leiomyomas , uterine malformations , adhesions in uterine endometrium. Hysteroscopy's benefit is shown in the way it provides us with direct vision to the uterus . Our Research is conducted around complications of hysteroscopy and its percentage . This research included 82 patients visited the department of obstetrics and gynecology with these complaints : infertility, abnormal uterine bleeding, menstrual disorders, recurrent abortions , Missing strings of IUDs . the complication rate of the hysteroscopy were ( 4.88% ) the most ommon complication was: bleeding ( 2.44% ) , it was the same rate of uterine perforation and acute abdominal pain ( 1.22% ) We never found any differences of complications rates According to different indications of hysteroscopy or according to the technique . As we found the Zero rate of vaginal delivery to the patient plays a role as a dangerous factor in the high rate of complications . Then , the Complication rate in our study are little, this explain that hysteroscopy is a safe procedure, and that push us to recommend to us it routinely which reduce the hospitalization time and the cost.